Street Legal Clinic: Development of Legal Learning Methods Based On Clinical Education in Law Education Institutions - Kadek Agus Sudiarawan; Putu Ade Harriestha Martana; Cok Istri Diah Widyantari Pradnya Dewi; I Kadek Wira Dwipayana; Luh Putu Budiarti (Fakultas Hukum Universitas Lampung, 2021)
Clinical Legal Education is an interesting subject to be developed at the Faculty of Legal, Universitas Udayana. Unlike other subjects, clinical legal education participants get an education in the classroom and go directly to the field (community) to increase students' knowledge and practical abilities in solving problems in society. The purpose of writing this journal is to find out how the form of clinical education-based learning, especially in the form of Street Legal Clinic at the Faculty of Law, Universitas Udayana, and to find a model for developing learning methods based on clinical legal education in the form of street legal clinic that can answer legal problems that develop in society. More optimally, the author uses normative legal research methods with the statutory approach and conceptual approach. The results showed that the form of the clinical legal education which is implemented at the Faculty of Law of Universitas Udayana consisted of three stages of the process, namely the planning component, the experiential component, and the reflection component with the learning models that had been used so far, namely In House Clinic, Out House Clinic, Combination and Street Legal Clinic. The development model suggested in implementing the Street Legal Clinic is to be more optimal in answering problems in the community, namely by accommodating several stages in its implementation, namely the pre-implementation, implementation, and evaluation stages into a single unit that is packaged creatively and comprehensively in collaboration with Clinical Partners.